Seroepidemiology of Fasciola Hepatica in Mersin province and surrounding towns and the role of family history of the Fascioliasis in the transmission of the parasite - Hakan ÖZTURHAN; Gürol EMEKDAŞ; Orhan Sezgin; Metin KORKMAZ; Engin ALTINTAŞ (Turkish Journal of Gastroenterology, 2019)
-